Phase III, randomised, double-blind, placebo-controlled trial of Neuroaspis plp10 as an adjuvant treatment for relapsing multiple sclerosis: the MINERAL Study - Paolo Preziosa; Maria A Rocca; Georgios Markozannes; Marios C Pantzaris; Paola Valsasina; Nikolaos Grigoriadis; Christos Bakirtzis; Georgios Hadjigeorgiou; Efthimos Dardiotis; George Loucaides; Evangelia Ntzani; Savvas Omorfos; et al. (BMJ Neurology Open, 2022)
Objectives To assess the effectiveness of Neuroaspis plp10 nutritional supplement when added to interferon (IFN)-β treatment in patients with relapsing-remitting multiple sclerosis (RRMS).Design A 30-month phase III multicentre, randomised, double-blind, placebo-controlled trial. Randomisation stratified by centre using a computer-generated procedure with Neuroaspis plp10 versus placebo in 1:1 ratio. The first 6 months were used as both the pre-entry and normalisation period.Setting 3 teaching hospitals in Greece and 1 Neurology Institute in Cyprus.Participants 61 patients with RRMS on IFN-β were randomly assigned to receive Neuroaspis plp10 (n=32) or placebo (n=29), 20 mL, orally, once daily, for 30 months.Intervention Neuroaspis plp10, a cocktail mixture, containing specific PUFA (12 150 mg) and γ-tocopherol (760 mg) versus virgin olive oil (placebo).Main outcome measure The primary end point was the annual relapse rate (ARR) whereas the secondary ones were the rate of sustained progression of disability, as measured by the Expanded Disability Status Scale (EDSS) and the brain T2 and gadolinium-enhancing lesions, at 2 years.Results For the intention-to-treat analyses Neuroaspis plp10 significantly reduced the ARR by 80%, (RRR, 0.20; 95% CI: 0.09 to 0.45; p=0.0001) and the risk of sustained progression of disability by 73% (HR, 0.27; 95% CI: 0.09 to 0.83; p=0.022) versus placebo, at 2 years. The number of T1 gadolinium-enhancing lesions and the number of new/enlarged T2-hyperintense lesions were significantly reduced (p=0.01 and p<0.0001, respectively). Both T1-enhancing and new/enlarging T2-hyperintense lesions were significantly reduced (p=0.05 and p<0.0001, respectively). No significant adverse events were reported.Conclusions Neuroaspis plp10 added to IFN-β was significantly more effective than IFN-β alone in patients with RRMS.Trial registration number ISRCTN06166891.